2013
DOI: 10.1016/j.juro.2012.08.201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the American Urological Association Annual Review Course on the Results of the Urology Qualifying Examination

Abstract: The majority of candidates are adequately prepared to pass their Qualifying Examination at the conclusion of their residency training program regardless of their attendance of the AUA Annual Review Course. This course may help bolster the confidence of the candidate preparing for their Qualifying Examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous studies have identified factors associated with board examination pass rates, such as review courses; structured remediation; examination preparation; country of training; and residency characteristics, including regional location, program size, residency accreditation cycle length, participation in examination simulations, and city population size . This study is the first of its kind to report physician preparation for the ABEM ConCert examination.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have identified factors associated with board examination pass rates, such as review courses; structured remediation; examination preparation; country of training; and residency characteristics, including regional location, program size, residency accreditation cycle length, participation in examination simulations, and city population size . This study is the first of its kind to report physician preparation for the ABEM ConCert examination.…”
Section: Discussionmentioning
confidence: 97%